Correlation of Blood Glucose Control With Cystoid Macular Edema and Central Macular Thickness After Cataract Surgery in Diabetics - Ding R; Wu B; Sun Y; Zhang X; Mi H; Kong Y; Ma Y (Clinical Ophthalmology)
Rui Ding, BaoHua Wu, Yan Sun, XiaoYan Zhang, HaiZhou Mi, YueRong Kong, YanGang Ma Department of Cataract Specialist, Lanzhou Bright Eyesight Hospital, Lanzhou City, Gansu Province, 730050, People’s Republic of ChinaCorrespondence: BaoHua Wu, Department of Cataract Specialist, Lanzhou Bright Eyesight Hospital, No. 111, Nanbinhe Middle Road, Qilihe District, Lanzhou City, Gansu Province, 730050, People’s Republic of China, Email purudr221@outlook.comObjective: Macular edema and retinal thickening after cataract surgery can lead to poor vision in patients, especially in the presence of high glucose. Blood glycosylated hemoglobin (HbA1c) concentration plays an important role in assessing diabetic control and is closely related to cataract surgery prognosis. The aim of this study was to investigate the correlation between postoperative HbA1c levels and postoperative cystoid macular edema (CME) and central macular thickness (CMT) in diabetic cataract patients.Methods: Retrospective analysis was conducted on 80 patients with diabetic cataracts from December 2018 to December 2023. The enrolled cases were divided into 2 groups according to the blood glucose control: 56 cases (56 eyes) in the intensive treatment group (HbA1c ≤ 7.0%) with insulin combined with oral hypoglycemic agents; and 24 cases (24 eyes) in the standard treatment group (HbA1c > 7.0%). The Student’s t-test or paired t-test was used to compare the changes in CMT between the two groups at each preoperative and postoperative time period. The chi-square test was used to compare the incidence of CME at each postoperative time period. Pearson or Spearman correlation was used to analyse the relationship between HbA1c levels and CMT or CME at each postoperative time period. Predictive efficacy was analyzed using ROC curves.Results: Patients who went through the standard treatment showed significant CMT thickening and CME at 3 and 6 months postoperatively. HbA1c levels were positively correlated with CME and CMT at 1, 3, and 6 months postoperatively, with good predictive efficacy.Conclusion: Postoperative HbA1c levels have a strong correlation with CME and CMT thickening and may be reliable and valid biomarkers.Keywords: blood glucose control, cystoid macular edema, retinal thickness, HbA1c